Indeks Performans (IP) dan Income Over Feed and Chick Cost (IOFCC) Penggunaan Biji Akasia Duri (Acacia nilotica (L.) Willd. ex Del.) Dengan atau Tanpa Fermentasi Dalam Pakan Ayam Kampung Super - Andi Simpursiah T.; Burhanuddin Sundu; Suharno H. Syukur (Universitas Tadulako, 2018)
The objective of this research is to determine Performance Index and Income Over Feed and Chick Cost (IOFCC) of super native chicken given fermented or unfermented of Acacia nilotica seed meal in the diet. The research was conducted at Sidera Village, Sigi Biromaru Sub District, Sigi Regency, Central Sulawesi Province. The research used Completed Random Design (CRD) with 5 dietary treatments and 4 replicate cages. The treatments are: P0: feed without acacia nilotica seed meal, P1: feed with 5% unfermented Acacia nilotica seed meal , P2 : feed with 10% unfermented Acacia nilotica seed meal , P3 : feed with 5% fermented Acacia nilotica seed meal , P4 : feed with 10% fermented Acacia nilotica seed meal. Analysis of variance indicated the effect of treatments on Performance Index was not significant (P>0,05). Means of Performance Index were 27,5 (P0), 35,3 (P1), 37,5 (P2,) 37,7 (P3) and 38,8 (P4). The effect of supplementation of treatments on Income Over Feed and Chick Cost (IOFCC) was highly significant (P < 0,01). Means of IOFCC were Rp. 7192 (P0), Rp. 12971 (P1), Rp. 15673 (P2), Rp. 13864 (P3) and Rp. 14982 (P4). In conclusion, effect of the addition of Acacia nilotica with/without fermention on super native chiken Performance Index was not significant. The effect of treatments on Income Over Feed and Chick Cost was highly significant. There is relationship between Performance Index and Income Over Feed and Chick Cost. Where treatment in low Performance Index, an also is lowproduce in Income Over Feed and Chick Cost.